ANALISIS RISIKO SALAH SAJI ATAS TRANSAKSI PIHAK BERELASI DALAM TRANSFER PRICING DOCUMENTATION PT XYZ - Thania Dwi Rahma; Ardhi Islamudin (Jurnal Ilmiah Akuntansi, 2026)
Related party transactions represent a high-risk area for material misstatement, particularly in the implementation of transfer pricing under abnormal market conditions. Transfer pricing practices that are inconsistent with the arm’s length principle may affect the fairness of financial statement presentation. This study aims to analyze the risk of misstatement arising from related party transactions from a transfer pricing perspective at PT XYZ. The study employs a qualitative case study approach through documentation analysis of transfer pricing documentation, financial statements, affiliated agreements, and relevant transfer pricing regulations. Data were analyzed descriptively through data reduction, data display, and conclusion drawing. The results indicate that affiliated sales transactions, related party loans, and management service transactions pose significant misstatement risks, particularly regarding fair pricing, expense recognition, and transaction comparability. Extraordinary market conditions in the palm oil industry also affected profitability and increased the complexity of transfer pricing evaluation. This study concludes that adequate transfer pricing documentation and consistent application of methods are essential in minimizing material misstatement risks in financial statements